ANALISIS ASPEK-ASPEK PENENTU DALAM PERTIMBANGAN NASABAH MEMILIH PRODUK PEMBIAYAAN DI BMT NU CABANG BUNGATAN SITUBONDO - Siti Nur Aini; Masyhuri Masyhuri; Umratul Khasanah (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2022)
The development of the Islamic economy and financial institutions in Indonesia appears to be showing significant progress, one of which is Baitul Maal Wal Tamwil (BMT) NU Bungatan Situbondo Branch. This institution has an important role because it can help and fulfill the wishes of some people, especially Muslims who want the services of Islamic financial institutions to manage their economy in accordance with Shari'a. But behind that, there are inhibiting factors as well as supporting factors that have made BMT NU able to survive amidst the many financial institutions that exist today. To collect the data, the researcher used several methods, namely observation, interviews and documentation, then the data were analyzed using qualitative descriptive analysis techniques. Based on this research, it can be concluded that there are several determinant aspects for customers in choosing financing products, one of which is customer satisfaction and trust. The development of a product is very much based on the trust of customers when the payment of installments increases sharply, indirectly the fear of consumers has haunted the large installments paid per month. Consumers or customers will pay attention to the quality of a bank, especially from the services and products offered. This motivates customers to use it carefully so as to create a sense of satisfaction for customers.